2022
DOI: 10.1055/s-0042-1760253
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Magnetic Resonance Imaging (Neurography) and Electrodiagnostic Study Findings with Intraoperative Findings in Post Traumatic Brachial Plexus Palsy

Abstract: Background The majority of brachial plexus injuries (BPIs) are caused by trauma; most commonly due to two-wheeler road accidents. It is important to determine whether the lesion in question is pre-ganglionic or post-ganglionic for purposes of surgical planning and prognosis. Diagnostic testing helps the surgeon to not only decide whether surgical intervention is required, but also in planning the procedure, thereby maximizing the patient's chances of early return to function. The aim of the study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Neuromas can be detected without administration of contrast material. In addition, MR myelography is a method that has been used for the demonstration of pseudomeningoceles (Patel et al., 2022).…”
Section: Advance: How Do Developments In Imaging and Electrodiagnosti...mentioning
confidence: 99%
“…Neuromas can be detected without administration of contrast material. In addition, MR myelography is a method that has been used for the demonstration of pseudomeningoceles (Patel et al., 2022).…”
Section: Advance: How Do Developments In Imaging and Electrodiagnosti...mentioning
confidence: 99%
“…Our group has shown that a combination of Edx and MRI increases the sensitivity and specificity of the diagnosis in adults. 9…”
Section: Indications For Primary Plexus Surgerymentioning
confidence: 99%
“…Our group has shown that a combination of Edx and MRI increases the sensitivity and specificity of the diagnosis in adults. 9 We routinely and regularly use imaging with MRI to document and follow up the shoulder deformity in terms of the angle of glenoid version as well as PHHA. After the age of 5, we shift to computed tomography (CT) of the shoulder for the same indication.…”
Section: Role Of Imagingmentioning
confidence: 99%